Business Development Strategy Selection for Cracker Enterprises with SWOT and ANP Approaches: Pemilihan Strategi Pengembangan Usaha Kerupuk dengan Pendekatan SWOT dan ANP - Ningrum, Antika Yuspita; Handayani, Nurlaila; Sabardi, Wiky (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2023)
Tiara Kerupuk Merah business is still relatively new and development is still needed. The amount of cracker production was less than the demand, this was due to limited human resources and production facilities that were stillnot optimal. From the existing problems, the Red Kerupuk Tiara Business requires a strategy to be able to overcome a problem and the business development process. The method used is SWOT (Strengths, Weaknesses, Opportunities,Threats) and ANP (Analytical Network Process). The results of the study from the SWOT analysis are that there are 6 (six) alternative strategies for developing the Red Tiara Kerupuk Business. The results of the ANP calculation are the first priority strategy with a value limit (0.057), namely opening branches in other locations/regions, the second priority strategy with a value limit (0.036), namely being a superior supplier for the restaurant industry, and the third priority strategy with a value limit ( 0.025) namely developing products to be distributed to supermarkets.